Faktor - Faktor yang Mempengaruhi Pemberian Asi Eksklusif di Puskesmas Mulyojati Metro Barat Kota Metro - Ike Ate Yuviska; Dewi Yuliasari; Devi Kurniasari (Universitas Malahayati Lampung, 2024)
ABSTRACT Exclusive breastfeeding is breastfeeding only for 6 months without additional food. According to WHO, in 2020, 44% of infants aged 0-6 months throughout the world were given exclusive breastfeeding. Coverage of exclusive breastfeeding in Lampung Province in 2020 (70.1%), Metro City District (78.7%) but the coverage of exclusive breastfeeding is still low at the Mulyojati Health Center (54.7%). Factors that influence exclusive breastfeeding are knowledge, age, education, and employment. The purpose of the research is to know the relationship between knowledge, age, education, and work regarding exclusive breastfeeding at the Mulyojati Metro Barat Health Center in 2023. This research method includes a type of quantitative research using a cross-sectional approach. The population and sample were mothers with infants aged 6-12 months, totaling 69, using a total sampling technique. Univariate and bivariate data analysis, statistical tests using chi-square test and logistic regression. The results of this study show the results of univariate analysis of 69 respondents, the majority (62.3%) of mothers gave exclusive breastfeeding, the majority (55.1%) of mothers had good knowledge, the majority (55.1%) of mothers aged 20-35 years, the majority (71.0%) of mothers are highly educated, the majority (58.0%) of working mothers. The results of the bivariate analysis showed that there was a relationship between knowledge (p=0.000 OR=9.697), age (p=0.016 OR=3.913), education (p=0.007 OR=5.143), occupation (p=0.006 OR=5.305). Suggestions for mothers, it is hoped that breastfeeding mothers will add knowledge, insight and seek as much information as possible about the correct way of breastfeeding and improve relationships between individuals who can later share information, experience and support each other in providing breastfeeding to their children. Keywords: Knowledge, Age, Education, Occupation, Exclusive Breastfeeding ABSTRAK ASI eksklusif adalah pemberian ASI saja selama 6 bulan tanpa makanan tambahan. Menurut WHO pada tahun 2020 yang memberikan ASI Eksklusif sebanyak 44% bayi usia 0-6 bulan disuluh dunia yang mendapatkan ASI Eksklusif Cakupan ASI eksklusif di Provinsi Lampung pada tahun 2020 (70,1%), Kabupaten Kota Metro (78,7%) namun cakupan pemberian ASI eksklusif masih rendah di Puskesmas Mulyojati (54,7%). Faktor yang mempengaruhi pemberian ASI eksklusif yaitu pengetahuan, umur, pendidikan, dan pekerjan. Tujuan penelitian Diketahui hubungan pengetahuan pengetahuan, umur, pendidikan, dan pekerjan tentang pemberian ASI Eksklusif di Puskesmas Mulyojati Metro Barat Tahun 2023. Metode penelitian ini termasuk Jenis penelitian kuantitatif dengan menggunakan metode pendekatan cros sectional. Populasi dan sampel adalah ibu bayi usia 6-12 bulan berjumlah 69, dengan teknik total sampling. Analisa data univariat dan bivariat, uji statistik menggunakan uji chi-square dan regresi logistik. Hasil penelitian ini menunjukan Hasil analisis univariat dari 69 responden sebagian besar (62,3%) ibu memberikan ASI eksklusif, sebagian besar (55,1%) ibu berpengetahuan baik, sebagian besar (55,1%) ibu umur 20-35 tahun, sebagian besar (71,0%) ibu berpendidikan tinggi, sebagian besar (58,0%) ibu bekerja. Hasil analisis bivariate menunjukan ada hubungan pengetahuan (p=0,000 OR=9.697), umur (p=0,016 OR=3.913), pendidikan (p=0,007 OR=5.143), pekerjaan (p=0,006 OR=5.305). Saran bagi ibu diharapkan para ibu menyusui menambah pengetahuan, wawasan dan mencari informasi yang sebanyakbanyaknya tentang cara menyusui yang benar serta meningkatkan hubungan antar individu yang nantinya bisa berbagi informasi, pengalaman serta saling mendukung dalam memberikan ASI kepada anaknya Kata Kunci: Pengetahuan, Umur, Pendidikan, Pekerjaan, ASI Eksklusif